Rectifiability of RCD(K,N) spaces via δ-splitting maps - Bruè, Elia; Pasqualetto, Enrico; Semola, Daniele (Annales Fennici Mathematici, 2021)
In this note we give simplified proofs of rectifiability of RCD(K,N) spaces as metric measure spaces and lower semicontinuity of the essential dimension, via \(δ\)-splitting maps. The arguments are inspired by the Cheeger-Colding theory for Ricci limits and rely on the second order differential calculus developed by Gigli and on the convergence and stability results by Ambrosio-Honda.